2004
DOI: 10.1111/j.1875-595x.2004.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in Kenya

Abstract: This paper gives general information on the location of Kenya, its demography, economy, organisation of health services, general health policy, health financing, oral health infrastructure, problems that hamper health financing and proposals on how to solve these problems. Further, a summary of health status of the Kenyan people is given based on the results of studies. The mean DMFT for the rural and urban populations is low and there is no evidence of an increase or decrease. Similarly, the prevalence of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…Despite, the relatively high occurrence of microbial plaque, dental calculus and gingival bleeding on probing, the prevalence of severe periodontal disease was low and corroborates with other findings in Tanzania, and neighboring country, Kenya [1-3,40,41]. Moreover, majority of the populations in Tanzania and Kenya retained most of their dentition in a functional state even up to the age of 65 years signifying that severe destruction of periodontal tissue is minimal [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…Despite, the relatively high occurrence of microbial plaque, dental calculus and gingival bleeding on probing, the prevalence of severe periodontal disease was low and corroborates with other findings in Tanzania, and neighboring country, Kenya [1-3,40,41]. Moreover, majority of the populations in Tanzania and Kenya retained most of their dentition in a functional state even up to the age of 65 years signifying that severe destruction of periodontal tissue is minimal [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…In this area, access to oral health facilities and trained oral health manpower is severely limited with no dentists, dental technologists and community oral health officers in rural clinics and dispensaries. This confirms a 2004 report [5] which reviewed the status of oral health services in Kenya and vividly revealed that 80 % of the dentists within the country were observed to be operating in urban centres.…”
Section: Availability Of Dentist and Dental Technologistssupporting
confidence: 70%
“…This study was conducted in a rural hard to reach area in Kenya identified as Il-Polei in Laikipia North, a region inhabited by nomadic pastoral communities, to assess the prevalence of dental caries in subjects attending a medical camp in 2014 organised by the Kenya Methodist University, School of Medicine and Health Sciences in collaboration with the sub-county community health officers through the Ministry of Health Services. This was partially in response to observations made in 2004, that there was scanty data on Communities' Dental Health Issues and Mitigating Morbidity Associated with Dental Caries rural prevalence of dental carries in Kenya as most reported studies were clustered around urban town centres [5]. Moreover, currently available data does not address the issues of whether or not dental problems are declining or increasing in Kenya.…”
Section: Introductionmentioning
confidence: 83%
“…In many developing countries, health care financing programs do not give priority to oral health. This results in a lack of national oral health policies and strategies of implementation (4,16). Several of these countries have a shortage of oral health personnel and lack facilities and equipment, materials, supplies and maintenance.…”
Section: Primary Health Carementioning
confidence: 99%